2020
DOI: 10.1042/bsr20193031
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the M2a macrophage-induced axonal regeneration of neurons by arginase 1

Abstract: Background: Spinal cord injury (SCI) is a challenge worldwide, but there are no effective treatments or therapeutic methods in the clinic. Recent studies have shown that type I arginase (Arginase1, Arg1) is closely associated with the treatment of SCI. The classical treatment for SCI involves filling the local area of SCI with activated M2a macrophages to allow the repair and regeneration of some synapses, but the specific mechanism of action of Arg1 is not clear. Method: In the present study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…5 F ). The presence of IL-4 significantly increased mRNA levels of the neuroprotective factor Arg1 ( 37 , 40 ) in untreated, control plasma–treated, and CAC-plasma–treated macrophages by 5.6-, 4.1-, and 3.2-fold, respectively ( Fig. 5 G ).…”
Section: Resultsmentioning
confidence: 92%
“…5 F ). The presence of IL-4 significantly increased mRNA levels of the neuroprotective factor Arg1 ( 37 , 40 ) in untreated, control plasma–treated, and CAC-plasma–treated macrophages by 5.6-, 4.1-, and 3.2-fold, respectively ( Fig. 5 G ).…”
Section: Resultsmentioning
confidence: 92%
“…Hence, the use of suitable methods to induce peri-implant nerve regeneration could be effective for improving proprioception of dental implants [ 142 ]. In addition, recent findings have related the polarization of M2 macrophages with the restoration of axonal regeneration [ 143 ], proving the functional links between the immune system and the nervous system [ 144 ]. Surprisingly, there is an M2 regulation in the peri-implant environment [ 2 , 31 , 111 ] and both neurofilament-positive fibers and nerve bundles have been observed near the titanium implant surface [ 63 , 145 ].…”
Section: Functional Integration Of Dental Implants After Achieving Thmentioning
confidence: 99%
“…Arg1 expression is increased in microglia/macrophages and astrocytes early after CNS injury [ 32 ]. Arg1 is considered a marker of beneficial microglia/macrophages and has anti-inflammatory and tissue repair properties in various pathological conditions [ 33 ]. Our experiments found that the content of Arg1 was significantly increased in PD, which may be due to the induction of NOS expression in the pathological state of brain tissue, resulting in excessive NO production.…”
Section: Discussionmentioning
confidence: 99%